Evolutionary and ontogenetic transformations of contractile cells: Adaptive and regulatory mechanisms - Kuibida, V.; Kokhanets, P. (Regulatory Mechanisms in Biosystems, 2026)
The appearance of muscle tissue is an important step in the evolution of animals, as it enabled them to disperse, escape, hunt, and explore new habitats. Modern contractile cells of animals form an evolutionary continuum - from the unspecialized contra c tile epithelium of placozoans, through the epithelium with supracellular actomyosin bundles, which are characteristic of modern sponges, to the epitheliomuscular tissues of sea anemones. The final link in this continuum was specialized muscle tissue, which has lost most or all of its epithelial properties and is represented in ctenophores, jellyfish, and bilaterians. The ontogeny of muscle tissue reflects the main stages of its phylogenetic evolution. In the course of evolution, animal muscle tissue was formed under the influence of a fundamental physiological limitation: the faster a muscle fiber contracts, the less economically it uses energy and the faster it tires. Therefore, a continuous functional series of striated fibers was formed in animals: type I → type IIa → type IIx → type IIb, which reflects a gradual transition from energy economy to maximum contraction speed. Different types of mu s cle fibers are not just histological variants of tissue, but different evolutionary strategies for using energy for movement. The diversity of muscle fiber types reflects a fundamental evolutionary compromise between the speed of contraction and the energy efficiency of muscle work. Within the framework of this compromise, a functional gradient of fibers from slow oxidative to maximally fast glycolytic fibers has formed, which ensures the implementation of different locomotion strategies in animals. During the evolutionary process, a general pattern of the functioning of the muscular system was formed: with an increase in the body weight of the animal, the maximum speed of muscle fiber contraction decreases. In contrast, in smaller rodents and pred a tors, the fastest glycolytic IIb fibers dominated, providing a high frequency of movements, fast reactions to short distances of movement. Therefore, the diversity of muscle fiber types is determined not only by metabolism, but also by the allometry of the body and the mechanics of movement.